PROSPEK PENGATURAN KOMISI KHUSUS PENYUSUN DAERAH PEMILIHAN DALAM PEMILIHAN UMUM LEGISLATIF MENURUT UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Hantoro, Bimo Fajar (Faculty of Law, Parahyangan Catholic University, 2023)
Electoral redistricting institution has a critical role in determining whether a proportional arrangement of electoral districts can be achieved. In Indonesia, there has been a disparity between electoral districts established by the House of Representatives (DPR) and the General Elections Commission (KPU), especially during the 2019 DPR Election. Using doctrinal and socio-legal approaches, this paper aimsto evaluate the prospect of establishing a separate boundary commission in accordance with the 1945 Constitution. The findings suggest that the establishment of a boundary commission as part of electoral management bodies is normatively feasible. However, it must meet the institutional requirements of being national, permanent, and independent. Independency has to be construed as the institution being impartial. By conferring the boundary delimitation authority to a boundary commission, not only would KPU's burden be reduced, it could also better ensure that the delimitation process adheres to the delimitation principles.